PENGEMBANGAN GAME EDUKASI UNTUK MENINGKATKAN KEMAMPUAN MOTORIK HALUS ANAK PRASEKOLAH BERBASIS ANDROID - Aryo Prasetya; Novramdan Ilham Alan; Ahmat Josi; Sidhiq Andriyanto (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2025)
Fine motor skill development in early childhood is a critical aspect requiring precise stimulation, yet current preschool educational challenges reveal limitations in skill development media. This research aims to develop an Android-based educational game called GELANG (Gerak Gemilang) to improve preschool children's fine motor skills. The research method employed the Game Development Life Cycle (GDLC) with six stages: initialization, pre-production, production, alpha testing, beta testing, and release. The game was designed using Unity Game Engine with three game types: puzzle, maze, and coloring, each featuring three difficulty levels. Data collection was conducted through questionnaires and observations at PAUD Kemuning Kecamatan Koba, involving 14 preschool children. Testing results showed the game achieved 92% expert validation, categorized as "Very Valid". Blackbox testing confirmed all game functions operated optimally, while beta testing indicated the game effectively enhances children's fine motor skills. GELANG has proven capable of creating an engaging interactive learning medium that supports hand-eye coordination development and stimulates children's creativity in an enjoyable manner.